PENYELESAIAN TINDAK PIDANA PENGANIAYAAN YANG DILAKUKAN OLEH GURU DI LINGKUNGAN SEKOLAH BERDASARKAN UNDANG-UNDANG NOMOR 35 TAHUN 2014 TENTANG PERUBAHAN ATAS UNDANG-UNDANG NOMOR 23 TAHUN 2002 TENTANG PERLINDUNGAN ANAK - Diana, Ledy; ', Nurcholis; ', Erdianto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
In Indonesia, the persecution of a teacher to the students in the schooloften happens because there are some reasons is about discipline and educatethat cause physical and psychological injuries. Type of abuse carried out by theteacher to his students as throws with eraser, ruler, dried in the field, dijewer andbeaten. Besides, the students also experienced psychological violence in the formof a shout and cuss words, like a dumb, stupid, skinny, skinny and so on. Casesthat occurred in the city of Great Wood, who committed the crime of persecutionagainst the fourth grade students in the State Primary School 2 Talbot District ofPedamaran Ogan Ogan Ilir on behalf of Hj. Ruslaini, S.Pd bint H. Hashim withthe Indictment No. Reg Case: PDM - 154 / K / Euh.2 / 07/2015, and the CriminalDecision No. 354 / Pid.sus / 2015 / PN Kag.Based on the research that the completion of the criminal acts ofpersecution carried out by teachers in schools based on Law No. 35 of 2014concerning amendments to the Law No. 23 of 2002 on the protection of children,especially children who is a pupil in the school when it became a victim ofpersecution conducted by teachers has been governed by Article 54 and Article 80of Law No. 35 of 2014 concerning amendments to the Law No. 23 of 2002 onChild Protection, after the regulations protect students in the school environment,teachers are unwilling to reprimand if the student made a mistake due to strictsanctions of the Law on Child Protection, while the efforts of the schools provideguidance to all teachers to establish the concept of educational child-friendly, theteachers discuss and establish agreements with students about the rules forstudents that are not orderly , socialization order for the students, forming acontainer socialization and regular communication with the parents, childfriendlyschool concept in every curriculum.Keywords : Settlement - persecution - Teachers - School